Perception of Philosophy Students on the Impact of Mobile Legends on Spiritual Growth of Students at the Faculty of Philosophy Surya Nusantara Adventist University - Yoanes Sinaga (Universitas Advent Surya Nusantara, 2025)
This research aims to understand the views of theology students on the use of Mobile Legends in their spiritual growth, identify the impacts of their Mobile Legends playing habits, and analyze whether these habits can hinder spiritual growth. This study uses a qualitative approach with observation, interview, and documentation methods. The research subjects were 14 philosophy students at Surya Nusantara Adventist University who have the habit of playing Mobile Legends. The results of this study indicate that Mobile Legends can have a negative impact on the spiritual growth of Philosophy students, such as experiencing a decline in spirituality due to game addiction, neglect of worship time and spiritual priorities, and the emergence of negative emotions while playing. Factors influencing this impact include personality, motivation, and gamingenvironment.